OP0296 Autoimmune associated gene PTPN22 negatively regulates DECTIN-1 signalling in dendritic cells. (15th June 2017) - Purvis, H; Clarke, F; Jordan, C; Sanchez-Blanco, C; Cornish, GH; Rawlings, D; Zamoyska, R; Cope, AP
Abstract : Background: A single nucleotide polymorphism within the phosphatase PTPN22 increases the risk of developing multiple autoimmune and connective tissue diseases. 1 Ptpn22 is a negative regulator of Syk and Src family kinases downstream of immuno-receptor signalling cascades. 2 Fungal β-glucan receptor dectin-1, signals via Syk kinase, and induces dendritic cells to secrete pro-inflammatory cytokines IL-1β, IL-6, IL-12/23p40 and TNFα, in turn allowing the induction of IL-17 secreting T-cell responses, which are critical to the clearance of fungal infections. 3 IL-17 has been implicated as a key cytokine in inflammatory responses associated with RA, JIA, and psoriasis. 4 Objectives: To investigate if Ptpn22 regulates dectin-1 signalling and controls the capability of dectin-1 matured BMDC to promote adaptive immune responses. Methods: GM-CSF bone marrow derived dendritic cells (BMDC) were generated from C57BL/6 WT, Ptpn22 -/- or Ptpn22 R619W (human PTPN22 R620W orthologue) mice, and pulsed with OVA323–339 in the presence or absence of the dectin-1 agonist curdlan. Activated BMDC were co-cultured in vitro with OT-II T-cells or adoptively transferred into OT-II mice and the resulting T-cell response assessed. Cytokine secretion from curdlan activated Ptpn22 variant mouse BMDC was determined by immunoassay and the kinetics of Syk and Erk phosphorylation were determined by immunoblot. Results: We observed that Dectin-1 activated Ptpn22 -/- BMDC had an enhanced capability to induce T-cell IL-17 secretion both in vitro and in vivo compared to WT BMDC. Following dectin-1 priming Ptpn22 -/- BMDC secreted increased IL-1β compared to WT BMDC, and the increase in IL-1β was found to be sufficient to cause the enhanced IL-17 response induced by Ptpn22 -/- BMDC. Dectin-1 induced IL-1β secretion was found to be Syk and Erk dependent and assessment of Syk and Erk kinetics of phosphorylation revealed that dectin-1 activated Ptpn22 -/- BMDC displayed enhanced Syk and Erk phosphorylation compared to WT BMDC. Furthermore, Ptpn22 R619W BMDC (orthologue of human Ptpn22 R620W ) exhibited a similar enhancement in IL-1β secretion and induced enhanced T-cell dependent IL-17 responses in vivo, indicating that the PTPN22 polymorphism behaves as a loss-of-function allele in the context of dectin-1 signals. Conclusions: Data highlight Ptpn22 as a novel regulator of dectin-1 signals and provide a link between genetically conferred perturbation to innate receptor signalling pathways and autoimmunity. References: Burn, G. L., Svensson, L., Sanchez-Blanco, C., Saini, M. & Cope, A. P. Why is PTPN22 a good candidate susceptibility gene for autoimmune disease? FEBS Lett. 585, 3689–98 (2011). Cloutier, J. F. & Veillette, A. Cooperative inhibition of T-cell antigen receptor signaling by a complex between a kinase and a phosphatase. J. Exp. Med. 189, 111–21 (1999). Dambuza, I. M. & Brown, G. D. C-type lectins in immunity: recent developments. Curr. Opin. Immunol. 32, 21–27 (2015). Tabarkiewicz, J., Pogoda, K., Karczmarczyk, A., Pozarowski, P. & Giannopoulos, K. The Role of IL-17 and Th17 Lymphocytes in Autoimmune Diseases. Arch. Immunol. Ther. Exp. (Warsz). 63, 435–49 (2015). Disclosure of Interest: None declared